EFEKTIVITAS MEDIA EDUKASI AUDIOVISUAL UNTUK MENINGKATKAN PENGETAHUAN PENCEGAHAN KECEMASAN PADA REMAJA DI SMAN 3 BOYOLALI - Azkiya, Najwa; Umaroh, Ayu Khoirotul (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Anxiety is something that everyone can experience when they feel something is threatening. According to the World Health Organization (WHO), 20% of the world's population suffers from anxiety, and as many as 48% of teenagers often feel anxious. Adolescents can experience anxiety if there are threats or disturbances experienced during the transition period. This community service activity aims to increase teenagers' knowledge about preventing anxiety. The method for implementing this activity is to provide education regarding anxiety prevention through audiovisual media. 36 class X students attended this activity. The results of this activity were that there was an increase in the average knowledge score of teenagers by 71.25 and an increase in the average knowledge score by 80.83 after providing education regarding anxiety prevention using audiovisual media.